Analisis Manajemen Risiko pada Bengkel Diesel Menggunakan Framework ISO 31000: Studi Kasus Bengkel Diesel Kubota di Jampang Kulon - Naila Dwi Ananti; Wafiyati Nur Amrina; Alifa Raudhatul Nisa; Umu Mahmudh; Alfiana (Indo Publishing, 2025)
This research analyzes risk management at Bengkel Diesel Kubota, a micro-scale MSME established in 2010 in Jampang Kulon, using the ISO 31000 framework. The study identifies critical risks through qualitative descriptive methods, including direct observation and in-depth interviews with the owner. Key findings reveal 15 risk events across 5 categories: financial (3), operational (4), human resources (3), supply chain (3), and customer-related (2). Risk assessment using a 3×3 matrix shows 2 high-level risks (financial instability and weather disruptions), 6 medium-level risks, and 7 low-level risks. The study recommends prioritizing financial management systems, supplier diversification, and SOP development to enhance business resilience